Targeting Autophagy in Innate Immune Cells: Angel or Demon During Infection and Vaccination? - Tao, Sha; Drexler, Ingo (Frontiers in Immunology, 2020)
Innate immune cells are the ‘doorkeepers’ in the immune system and are important for the initiation of protective vaccine responses against infection. Being an essential regulatory component of the immune system in these cells, autophagy not only mediates pathogen clearance and cytokine production, but also balances the immune response by preventing harmful overreaction. Interestingly, recent literature indicates that autophagy is positively or negatively regulating the innate immune response in a cell type-specific manner. Moreover, autophagy serves as a bridge between innate and adaptive immunity. It is involved in antigen presentation by delivering pathogen compounds to B and T cells, which is important for effective immune protection. Upon infection, autophagy can also be hijacked by some pathogens for replication or evade host immune responses. As a result, autophagy seems like a double-edged sword to the immune response, strongly depending on the cell types involved and infection models used. In this review, the dual role of autophagy in regulating the immune system will be highlighted in various infection models with particular focus on dendritic cells, monocytes/macrophages and neutrophils. Targeting autophagy in these cells as for therapeutic application or prophylactic vaccination will be discussed considering both roles of autophagy, the ‘angle’ enhancing innate immune responses, antigen presentation, pathogen clearance and dampening inflammation or the ‘demon’ enabling viral replication and degrading innate immune components. A better understanding of this dual potential will help to utilize autophagy in innate immune cells in order to optimize vaccines or treatments against infectious diseases.